New code structure for spectral amplitude coding in OCDMA system - Hasoon, Feras N.; Aljunid, S. A.; Abdullah, Mohammad Khazani; Shaari, Sahbudin (The Institute of Electronics, Information and Communication Engineers, 2007)
A new code structure for spectral amplitude coding optical code division multiple access system based on Double Weight (DW) code families is proposed. The DW code has a fixed weight of two. Modified Double Weight (MDW) code possesses ideal cross-correlation properties and the weight can be any even number, which is grater than two. The MDW code possesses ideal cross-correlation properties and exists for every natural number n. Using the MDW code compared to the existing codes such as Hadamard and Modified Frequency-Hopping (MFH) codes canprovide a much better performance. This has been demonstrated from the experiment simulation.